2004
DOI: 10.1262/jrd.50.675
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Hormonal Profiles in rdw Rats with Congenital Hypothyroidism Accompanying Increased Testicular Size and Infertility in Adulthood

Abstract: Abstract. Congenital hypothyroid mutant male rdw rats have enlarged testes in adulthood with dwarfism accompanied by infertility. To explain how rdw rats acquire enlarged testes in adulthood, we compared age-matched normal (N) rats at various developmental stages for blood levels of hormones, thyroxine (T4), follicle stimulating hormone (FSH), luteinizing hormone (LH) and testosterone (T), and investigated whether T4 therapy (rdw+T4) from 3 weeks of age (w) until adulthood could induce recovery of fertility in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 43 publications
2
20
2
1
Order By: Relevance
“…In Sprague Dawley rats, serum testosterone level began to increase at about 3 weeks of age and continue to rise until adult levels at about 10 weeks of age (Korenbrot et al, 1977;Chan et al, 1981). On the other hand, serum testosterone increased from 7 weeks of age and was maximal at 13 weeks of age in Wistar rats (Umezu et al, 2004). Together with these reports, the current study suggests that there might be an age-related difference in testosterone production between the two strains and this difference would affect the timing of sperm maturation.…”
Section: Discussionmentioning
confidence: 97%
“…In Sprague Dawley rats, serum testosterone level began to increase at about 3 weeks of age and continue to rise until adult levels at about 10 weeks of age (Korenbrot et al, 1977;Chan et al, 1981). On the other hand, serum testosterone increased from 7 weeks of age and was maximal at 13 weeks of age in Wistar rats (Umezu et al, 2004). Together with these reports, the current study suggests that there might be an age-related difference in testosterone production between the two strains and this difference would affect the timing of sperm maturation.…”
Section: Discussionmentioning
confidence: 97%
“…In the rdw rat, the thyroxine (T 4 ) levels in serum are drastically decreased [19,21,23], but the thyroid-stimu-…”
Section: Abstract: Growth Rdw Rat Thyroid Therapymentioning
confidence: 99%
“…Thus, we concluded that the rdw rat has primary hypothyroidism. Umezu et al have recently shown that male rdw rats show recovery of body weight with fertility in response to T 4 supplementary therapy from 3 weeks of age until adulthood [24].…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations